Mindfulness and tourism: The case of Madurese cultural heritage sites - Suryandari, Nikmah; Rahmawati, Farida Nurul (Universitas Bunda Mulia, 2023)
Mindful tourists are able to appreciate and understand heritage sites better than those who are mindless. Mindfulness is a concept that helps tourists build interpretations that will improve the quality of the experience and create a sustainable relationship between tourists and heritage sites. Mindful travellers are those who are actively engaged with interpretations of heritage sites that result in greater learning and understanding. In contrast, a mindless individual is one who follows a routine, pays limited attention to what he does and is stuck in a rigid mindset. Thus, this study aims to identify, build and validate measures of mindfulness in the context of cultural heritage tourism. This research uses quantitative research methods and is carried out in the Madura region which has cultural heritage tourism potential. The question items used to measure mindfulness were developed based on an extensive review of past literature. The data was collected through the distribution of questionnaires to 150 local Madurese and non-Madurese tourists.. The results revealed from this study show four different factors in measuring mindfulness, namely curiosity and attention, alertness, emotional involvement and openness and flexibility. The findings derived from this study offer new insights in understanding the concept of mindfulness